Anger and Approach Reply to Watson (2009) and to Tomarken and Zald (2009). [article]. - Carver, Charles S.
C. S. Carver and E. Harmon-Jones (2009) reviewed evidence consistent with the idea that anger arises from a behavioral approach system. Commentary on that article by A. J. Tomarken and D. H. Zald (2009) raised questions about many elements involved in acts of approach and limitations on what information can be provided by electroencephalograms. Commentary by D. Watson (2009) raised questions about the intensive psychometric evidence ilnking the negative affects. This article responds brieftly to -- (from the author)
Keywords: Anger; Approach; Electroencephalogram; Affect; Mood